IMPLEMENTATION OF LoRa SIGNAL DISTRIBUTION IN TRAFFIC LIGHTS - Ruslan, Ruslan (Telecommunications, Computers, and Electricals Engineering Journal (TELECTRICAL), 2025)
The development of wireless communication technology based on the Internet of Things (IoT) encourages the modernization of various urban infrastructures, including traffic light systems. This research discusses the implementation of Long Range (LoRa) technology as a wireless communication medium to control traffic lights in the four intersection area. LoRa was chosen because it has a wide transmission range, low power consumption, and ease of integration in smart city systems. The designed system consists of one ESP32 microcontroller-based transmitter and four receivers using NodeMCU ESP8266, which are connected through LoRa SX1278 module with frequency 433 MHz. Tests were conducted under Line of Sight (LOS) conditions with a distance variation of 25 meters to 125 meters. The performance parameters measured include Received Signal Strength Indicator (RSSI), Signal to Noise Ratio (SNR), and delay time. The test results show that as the distance increases, the RSSI and SNR values tend to decrease, but the system is still able to run three traffic light operation modes, namely normal, flash, and all-red operations, in real-time without significant interference up to a distance of 125 meters. This implementation proves that LoRa can be an effective and efficient solution for wireless communication-based traffic light systems, with the advantages of flexibility, low installation costs, and easy integration into modern traffic management systems.